2020
DOI: 10.3390/insects11110801
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Novel Adult Mass-Rearing Cage for Aedes albopictus (Skuse) and Anopheles arabiensis (Patton)

Abstract: Successful implementation of the sterile insect technique (SIT) against Aedes albopictus and Anopheles arabiensis relies on a continuous supply of sterile males. To meet this requirement, optimization of the mass-rearing techniques is needed. This study, therefore, aims to assess a new mass-rearing cage (MRC) in terms of egg production efficiency and egg hatch rate (quality). In addition, adult survival was evaluated based on a cage adult-index for Ae. albopictus. Moreover, the cage’s suitability for use in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…This methodology was used because the objective of the presented values was to evaluate the productivity of the rearing cages in a routine mass-rearing context. The survival of females was similar to that reported by Maiga et al [ 56 ] with a comparable methodology (88.5%). In our colony, the mortality of males was higher than females.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This methodology was used because the objective of the presented values was to evaluate the productivity of the rearing cages in a routine mass-rearing context. The survival of females was similar to that reported by Maiga et al [ 56 ] with a comparable methodology (88.5%). In our colony, the mortality of males was higher than females.…”
Section: Discussionsupporting
confidence: 89%
“…According to Balestrino et al [ 53 ], medium-sized cubic cages, such as the ones used in our program, are similar in productivity to large space-optimized cages, and Zhang et al [ 48 ] found that short cages allow for higher blood-feeding rates and egg production. The vertical resting surface density (1.56 mosquitoes/cm 2 ) was similar to the optimal density proposed by Zhang et al [ 47 ] (1.48 mosquitoes/cm 2 ), although both are high compared to the density of 0.8 mosquitoes/cm 2 used in similar experiments [ 53 , 54 , 56 ]. It should be noted that the results may have been affected by the method of estimating the number of produced eggs.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The most expensive component in the standard IAEA-BY mosquito larval diet developed by the international atomic energy agency (IAEA) [ 36 , 37 ] is the dehydrated bovine liver powder. Several studies focused on the reduction or replacement of the most expensive components were carried out [ 36 , 38 , 39 , 40 , 41 , 42 , 43 ]. Although very efficient, diets containing bovine liver powder were too expensive for the continuous process of mass rearing.…”
Section: Introductionmentioning
confidence: 99%